PENGEMBANGAN MEDIA PEMBELAJARAN BUKU CERPEN BERBASIS PENDEKATAN SOMATIC, AUDITORY, VISUAL, INTELEKTUAL (SAVI) BAGI SISWA KELAS IV SDN 53 PALEMBANG - Citra, Ayu Lia; Rizhardi, Rury; Hermansyah, Hermansyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low reading comprehension ability of fourth-grade students at SDN 53 Palembang, particularly in understanding the content of short stories, determining the main idea, and concluding the stories read. This study aims to develop a learning medium in the form of a short-story book based on the Somatic, Auditory, Visual, and Intellectual (SAVI) approach that meets valid and practical criteria for use in Indonesian language learning for fourth-grade elementary school students. The research method used is Research and Development (R&D) applying the 4D model, which consists of four main stages: Define, Design, Develop, and Disseminate. The short-story book medium was designed using the Canva Premium application in A5 size, integrating interactive activities based on the SAVI approach, including physical-activity columns, speaking/listening instructions, coloured illustrations, and reflective-thinking challenges. The results showed that the level of product validity based on expert assessment obtained an average percentage of 93.93%, categorised as very valid, while the practicality test through one-to-one and small-group evaluations obtained average percentages of 94.44% and 89.83% respectively, both categorised as very practical. Based on these results, it can be concluded that the SAVI-based short-story book learning medium is feasible, valid, and practical for use as an innovative supporting medium to increase student engagement and reading comprehension in Indonesian language learning at the elementary school level.